Analysis on the degree of freedom of interference alignment in cognitive radio - UNXian S; HAOXiao-hui Z (Tongxin xuebao)
The feasibility conditions were still unclear in the case of finite number of signal dimension for most cognitive radio systems. The IA problem of CR system with multiple primary users and multiple secondary users was divided into two sub-problems: the IA problem of primary network and the IA problem of secondary network, based on the cognitive mind. Then, the necessary IA conditions of secondary network were presented (good IA conditions of primary network have been proposed in previous research). Through the necessary conditions, it can obtain the upper bound of the average Dof of the secondary users. An improved minimum interference leakage algorithm was proposed, with which the conclu-sion was verified.